Effects of clear aligners treatment in growing patients: a systematic review - Vincenzo D’Antò; Vittoria De Simone; Silvia Caruso; Paolo Bucci; Rosa Valletta; Roberto Rongo; Rosaria Bucci (Frontiers in Oral Health)
IntroductionIn recent years, the use of Clear aligners (CA) has been diffused among children and adolescents. This systematic review aimed to summarize the literature regarding the effects of CA therapy in growing patients, including dentoalveolar and skeletal effects, periodontal changes, and quality of life measurements.MethodsAn electronic search on four databases was performed until September 2023, and studies including patients <18 years, treated with CA were selected. Studies with less than 10 patients and in vitro/laboratory studies were excluded. Study selection, data extraction, and risk of bias assessment were independently performed by two reviewers. The “Risk of Bias 2” (RoB 2) and the “Risk of Bias in Non-randomized Studies of Interventions” (ROBINS-I) tools were applied to assess the methodological quality of the included studies. Due to the heterogeneity in methodologies and outcomes encountered in the included studies, a qualitative synthesis of the results was provided.Results and conclusionsThe search resulted in 32 papers (3 RCTs), with sample sizes ranging between 15 and 113. The overall risk of bias in the RCT was low, while the risk of bias in the non-RCT ranged between moderate and serious for most of the included studies. Dentoskeletal and periodontal effects were the most frequently reported outcomes. The most common comparison group was multibracket fixed therapy, while only 5 studies had an untreated control group. Significant changes in the transversal maxillary arch width after treatment with CA were reported in some studies. However, while dentoalveolar effects have been reported consistently, controversial findings were found regarding the changes in skeletal bases after treatment with CA. Concerning the results on the sagittal plane, the current literature does not support the effectiveness of CA with mandibular advancement features in correcting dentoskeletal Class II, compared to traditional functional orthopedic appliances. In the short-term evaluation, periodontal variables and bacterial levels seemed to be better controlled during CA therapy, compared to the fixed multibracket therapy. With regard to quality of life measurements, there are inconsistent findings to support differences between CA therapy and fixed multibracket appliances. Nevertheless, additional high-quality studies are required to formulate more reliable conclusions.Systematic Review Registrationhttps://osf.io/wmerq.